Efficient system of homologous RNA recombination in brome mosaic virus: sequence and structure requirements and accuracy of crossovers. - Nagy, P D (1995)
Brome mosaic virus (BMV), a tripartite positive-stranded RNA virus of plants engineered to support intersegment RNA recombination, was used for the determination of sequence and structural requirements of homologous crossovers. A 60-nucleotide (nt) sequence, common between wild-type RNA2 and mutant RNA3, supported efficient repair (90%) of a modified 3' noncoding region in the RNA3 segment by homologous recombination with wild-type RNA2 3' noncoding sequences. Deletions within this sequence in RNA3 demonstrated that a nucleotide identity as short as 15 nt can support efficient homologous recombination events, while shorter (5-nt) sequence identity resulted in reduced recombination frequency (5%) within this region. Three or more mismatches within a downstream portion of the common 60-nt RNA3 sequence affected both the incidence of recombination and the distribution of crossover sites, suggesting that besides the length, the extent of sequence identity between two recombining BMV RNAs is an important factor in homologous recombination. Site-directed mutagenesis of the common sequence in RNA3 did not reveal a clear correlation between the stability of predicted secondary structures and recombination activity. This indicates that homologous recombination does not require similar secondary structures between two recombining RNAs at the sites of crossovers. Nearly 20% of homologous recombinants were imprecise (aberrant), containing either nucleotide mismatches, small deletions, or small insertions within the region of crossovers. This implies that homologous RNA recombination is not as accurate as proposed previously. Our results provide experimental evidence that the requirements and thus the mechanism of homologous recombination in BMV differ from those of previously described heteroduplex-mediated nonhomologous recombination (P. D. Nagy and J. J. Bujarski, Proc. Natl. Acad. Sci. USA 90:6390-6394, 1993).